Evaluation of phenolic profiles and antioxidant capacity of maqui (Aristotelia chilensis) berries and their relationships to drying methods. (13th March 2018) - Quispe‐Fuentes, Issis; Vega‐Gálvez, Antonio; Aranda, Mario
Abstract: BACKGROUND: Five drying methods (freeze, convective, sun, infrared, and vacuum drying) were applied to maqui berries to establish their effect on phenolic compounds and antioxidant capacity. Total phenolic, total flavonoid, and total anthocyanin contents were measured by spectrophotometry, anthocyanin and phenolic profiles were analyzed by chromatography, and the antioxidant capacity was determined. This study is probably the first to demonstrate the variation and stability of bioactive compounds from maqui berries after applying different drying methods. RESULTS: The highest content of phenolic and antioxidant compounds was obtained by using the freeze‐drying method compared with fresh samples ( P < 0.05). Eight anthocyanins were identified in all dehydrated maqui samples. Compared with fresh maqui, freeze‐dried samples retained 73% and 64% of delphinidin and cyanidin derivatives respectively. Sun‐ and vacuum‐dried samples conserved some phenolic acids. Vacuum‐dried maqui retained a higher amount of free flavonols. CONCLUSION: This study demonstrated that the application of any drying method results in a final product with good levels of phenolic compounds. © 2018 Society of Chemical Industry